The role of gut microbiota and drug interactions in the development of colorectal cancer - Wu, Jinna; Xia, Cong; Liu, Can; Zhang, Qianshi; Xia, Chenglai (Frontiers in Pharmacology, 2023)
The human gut microbiota is a complex ecosystem regulating the host’s environmental interaction. The same functional food or drug may have varying bioavailability and distinct effects on different individuals. Drugs such as antibiotics can alter the intestinal flora, thus affecting health. However, the relationship between intestinal flora and non-antibiotic drugs is bidirectional: it is not only affected by drugs; nevertheless, it can alter the drug structure through enzymes and change the bioavailability, biological activity, or toxicity of drugs to improve their efficacy and safety. This review summarizes the roles and mechanisms of antibiotics, antihypertensive drugs, nonsteroidal anti-inflammatory drugs, lipid-lowering drugs, hypoglycemic drugs, virus-associated therapies, metabolites, and dietary in modulating the colorectal cancer gut microbiota. It provides a reference for future antitumor therapy targeting intestinal microorganisms.